Historical and new insights into pathogenesis of type 1 diabetes. (15th November 2019) - Wong, F S; Tree, T I
Summary: In recent years, there have been exciting new insights into pathogenesis of type 1 diabetes in a number of areas of immunology. In this edition, a collection of four review articles are presented, which encompass new findings presented at the Immunology of Diabetes Society meeting in London 2018. The articles are focused particularly in 4 related areas of investigation, which include autoantibodies in type 1 diabetes, new autoantigenic targets for CD4 T cells, trafficking of immune cells to the pancreas and islet-immune interactions in the pancreas.